PERBERDAYAAN IBU-IBU PKK MELALUI KARAK TANPA BORAKS - Argoto Mahayana; Sunardi Sunardi; Muhammad Dzakwan; Widi Hariyanti; Sugiyarmasto Sugiyarmasto; Waluyo Budi Atmoko (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The partners in the Community Service Programme activities are the mothers of RT 1 RW 8 Jumok Jaten. Partners are housewives who have been affected by the Covid 19 pandemic because most of them were laid off by the company. Partners have the opportunity to produce karak without borax. The problems faced by partners are: 1) Lack of knowledge of PKK mothers about the dangers of borax; 2) Limited knowledge and skills about making karak without borax; and 3) Limited knowledge and skills about food safety and packaging. The method that will be carried out to realise the objectives of the Community Service implementation programme is through: 1) Making karak without borax; 2) Financial management training; 3) Marketing management training. The results obtained by the partners were able to make karak without borax which has a compact texture, crispy, and savoury taste, making it safe for consumption.